Tracing Sentinel Lymph Nodes and Inhibiting Lymphatic Metastasis with TiN Nanobipyramids Through Photothermal Therapy - Xu YN; Bai X; Chen JL; Wu X; Yin D; Yuan G; Dai R; Zhu XM; Wang J (International Journal of Nanomedicine)
Yan-Neng Xu,1,* Xiaopeng Bai,2,* Jian-Li Chen,3,* Xuan Wu,1 Dan Yin,1 Gang Yuan,1 Rongyang Dai,4 Xiao-Ming Zhu,1,5 Jianfang Wang2 1State Key Laboratory of Quality Research in Chinese Medicines, Macau Institute for Applied Research in Medicine and Health, Macau University of Science and Technology, Taipa, Macau SAR, 999078, People’s Republic of China; 2Department of Physics, The Chinese University of Hong Kong, Shatin, Hong Kong SAR, 999077, People’s Republic of China; 3Modern Research Center for Traditional Chinese Medicine, Shanxi University, Taiyuan, Shanxi, 030006, People’s Republic of China; 4Department of Biochemistry and Molecular Biology, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of China; 5Zhuhai MUST Science and Technology Research Institute, Macau University of Science and Technology, Zhuhai, Guangdong, 519099, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiao-Ming Zhu, State Key Laboratory of Quality Research in Chinese Medicines, Macau Institute for Applied Research in Medicine and Health, Macau University of Science and Technology, Taipa, Macau SAR, 999078, People’s Republic of China, Email xmzhu@must.edu.mo Jianfang Wang, Department of Physics, The Chinese University of Hong Kong, Shatin, Hong Kong SAR, 999077, People’s Republic of China, Email jfwang@phy.cuhk.edu.hkBackground: The lymphatic system is the major route of cancer metastasis, and sentinel lymph nodes (SLNs) are the first station for the spread of cancer cells. Accurate identification of SLNs by tracers during surgery is crucial for SLN biopsy and lymphadenectomy. However, conventional monomodal tracers such as blue dyes and carbon nanoparticles often induce a misjudgment of SLNs and thus are still unsatisfying for clinical applications. In addition, SLN imaging agents with therapeutic capabilities to achieve perfect theranostics have been less exploited.Purpose: Titanium nitride (TiN) nanostructures have the advantages of high stability and low cost and show superior plasmonic properties over both the visible and near-infrared (NIR) regions. Herein we report on the synthesis of TiN nanobipyramids (NBPs) with large sizes for multimodal SLN mapping.Methods: A hydrothermal method and post nitridation treatment were used to prepare the TiN NBPs. Bright- and dark-field imaging of SLNs with TiN NBPs were performed. The effect of TiN NBP size on SLN tracing was studied. The effect of TiN NBP-based photothermal ablation of SLNs combined with removal of primary tumors on pulmonary metastasis was studied.Results: The TiN NBPs with dual bright- and dark-field imaging functions show high drainage in lymph nodes and thus can act as a potential substitute for SLN tracing. Moreover, owing to the superior plasmonic properties of TiN nanostructures, the produced TiN NBPs show a high photothermal conversion efficiency under 1064 nm laser irradiation. TiN NBP-based photothermal ablation of metastatic LNs in the second NIR window (NIR-II) combined with surgical removal of primary tumors shows remarkable inhibition of pulmonary metastasis.Conclusion: This study not only demonstrates TiN NBPs as a new tracer for SLN mapping, but also presents a strategy for the photothermal ablation of lymph nodes in NIR-II for the inhibition of lymphatic metastasis.Keywords: TiN nanobipyramids, sentinel lymph nodes, lymph node mapping, photothermal therapy, second near-infrared window